Effect of axial electric field on confined water in carbon nanotube: Enhancement of thermophoresis. (July 2022) - Dang, Hao; Song, Dongxing; Lin, Zizhen; An, Meng; Ma, Weigang; Zhang, Xing
Highlights: It is clarified that the electric field plays an auxiliary role rather than a direct driving role in migration. The velocity of thermophoresis is enhanced by 99% by applying the axial electric field. The water molecules in carbon nanotube will carry out internal orderly collective movement under the axial electric field. This enhancement phenomenon is explained from the internal mechanism of hydrogen bond and friction coefficient. ABSTRACT: Strengthening the thermophoresis of nanoscale confined liquid is an intrinsic topic in nanoscale devices and systems. Unfortunately, enhancing thermophoresis via an uncontacted way is still ambiguous, while is quite desirable in technology. In this work, we propose a feasible strategy to enhance the thermophoresis of confined nano-liquid via using external electric field. Moreover, this strategy is demonstrated by a striking case, namely the electric field-intensified thermophoresis of the confined nano-liquid within carbon nanotube, with the aid of molecular dynamics simulation. The interfacial water molecules undergo a configuration transition from the disorder-like to the ordered network-like under the directional electric field-induced hydrogen bond interactions. As a result, the thermophoresis depicts a regular movement under electric field and the velocity increase as high as 99% is also achieved. This work illustrates a great promising potential in seawater desalination, cellular uptake and drug carrier, and nanofiltration membranes.